A Physical and sensorial characteristics of avocado spread added with different types of food hydrocolloids - Panyoyai, Naksit; Inta, Kanyalak; Gateam, Sudarat; Boonraeng, Supot (Indonesian Food Science and Technology Journal, 2018)
Avocado spread is an alternative condiment for a healthy consumption due to the abundance of unsaturated fatty acids in the avocado flesh. The avocado spread mixed with food hydrocolloids (guar gum, inulin, carboxymethyl cellulose) at 3% (w/w) was studied on rheology, texture, colour and sensory evaluation in comparison with no hydrocolloid addition. For the flow analysis, all spread formulations are the non-Newtonian shear thinning fluids. Addition of food hydrocolloids increased the viscosity, oscillation stability, and heat resistance. Inclusion guar gum with the fruit spread strongly affected the hardness and work of shear. The avocado spread added with inulin showed higher greenness than the other treatments. Among the spread samples containing 3% carboxymethyl cellulose secured the highest score for spreadability, colour, flavour, taste, and overall acceptability